Overlapping Map Penggunaan Overlapping Map dari Hasil Pengerjaan Reading Comprehension pada Aplikasi Viat – Map - Zahri, Riris Silvia; Andoko, Banni Satria; Amalia, Eka Larasati (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
The development of learning with technology continues to grow rapidly. Learning English especially Reading Comprehension in learning English for students is quite a big challenge. Viat-map is a web-based application that implements the Toulmin Argument concept for use in English Reading Comprehension subject. User acceptance of the Viat-Map application is one of the factors that supports the continued use of the application. Measurement of user acceptance of the Viat-Map application is carried out using the TAM (Technology Acceptance Model) method. This study aims to evaluate the implementation of the Viat-Map application using the TAM method, so that user perceptions and the factors that influence users in using the application can be identified. The research method uses a questionnaire as a tool to collect data on 26 users of the Viat-Map application. The results showed that user acceptance of the Viat-Map application had a positive effect on 3 TAM variables, namely perceived user convenience 89.56%, perceived usefulness 86.68%, and technology acceptance 81.87%. This shows that application developers can focus on improving development on the Viat-Map application acceptance variable because the percentage variable value is smaller than the other variable values. Keywords : Toulmin Argument, Viat-Map, Technology Acceptance Model